ARAB-MUSLIM PHILOSOPHY (Web of Teachers: Inderscience Research, 2025)
The tradition of philosophical reflection, which arose and developed during the era of the dominance of the Islamic worldview in a predominantly Arabic-speaking civilization and has undergone a significant transformation in our days under the influence of Western civilization and philosophy.